COVID‐19 pneumonia in kidney transplant recipients: A promising treatment algorithm in the absence of a disease‐specific drug. Issue 10 (6th June 2021) - Karatas, Murat; Tatar, Erhan; Simsek, Cenk; Yıldırım, Ali Murat; Ari, Alpay; Zengel, Baha; Uslu, Adam
Abstract: There is no consensus on the management of coronavirus disease 2019 (COVID‐19) and modification of immunosuppressive therapy in kidney transplant recipients (KTRs). In this study, we examined the clinical outcome of our KTRs with COVID‐19 disease, who were treated with a broad‐spectrum anti‐inflammatory protocol. This protocol is essentially composed of intravenous immunoglobulin +/‐ tocilizumab in KTRs with severe COVID‐19 pneumonia. Among 809 KTRs, 64 patients diagnosed with COVID‐19 disease between April 2020 and February 2021, were evaluated. Twenty‐nine patients with pneumonia confirmed by chest computed tomography (CCT) were hospitalized. The treatment protocol included high‐dose intravenous methylprednisolone, favipiravir, enoxaparin, and empirical antibiotics. Patients with pneumonic involvement of more than 25% on CCT with or without respiratory failure were given a total of 2 g/kg intravenous immunoglobulin (IVIg) therapy. Nonresponders received tocilizumab, an interleukin‐6 receptor antibody. Of the 29 patients with pneumonia, 6 were treated in other hospitals. These six patients did not receive IVIg and 5 of them deceased. In our center, IVIg treatment was applied to 15 of 23 patients. Seven of them required tocilizumab. Respiratory parameters improved significantly in all but one patient after IVIg ± tocilizumab treatment. The mortality rate was 6.6% in patients who received IVIg therapy and 35.7% in those who did not ( p = 0.08). The mortality rate was higher in patients who received treatment in external centers (2.2% vs. 26.3%; p = 0.0073). The treatment of KTRs with severe COVID‐19 pneumonia in organ transplant centers with significant experience yields better results. The administration of broad‐spectrum anti‐inflammatory treatment in this patient group was safe and provided excellent outcomes.